Pr‐favoured variants of the bacteriophytochrome from the plant pathogen Xanthomonas campestris hint on light regulation of virulence‐associated mechanisms. (2nd May 2021) - Conforte, Valeria; Otero, Lisandro Horacio; Toum, Laila; Sirigu, Serena; Antelo, Giuliano Tomás; Rinaldi, Jimena; Foscaldi, Sabrina; Klinke, Sebastián; Chavas, Leonard Michel Gabriel; Vojnov, Adrián Alberto; Goldbaum, Fernando Alberto; Malamud, Florencia; et al.
Abstract : Red/far‐red light‐sensing bacteriophytochrome photoreceptor (BphP) pathways play key roles in bacterial physiology and ecology. These bilin‐binding proteins photoswitch between two states, Pr (red absorbing) and Pfr (far‐red absorbing). The isomerization of the chromophore and the downstream structural changes result in the light signal transduction. The agricultural pathogen Xanthomonas campestris pv.  campestris ( Xcc ) code for a single bathy‐like type BphP ( Xcc BphP), previously shown to negatively regulate several light‐mediated biological processes involved in virulence. Here, we generated three different full‐length variants with single amino acid changes within its GAF domain that affect the Xcc BphP photocycle favouring its Pr state: L193Q, L193N and D199A. While D199A recombinant protein locks Xcc BphP in a Pr‐like state, L193Q and L193N exhibit a significant enrichment of the Pr form in thermal equilibrium. The X‐ray crystal structures of the three variants were solved, resembling the wild‐type protein in the Pr state. Finally, we studied the effects of altering the Xcc BphP photocycle on the exopolysaccharide xanthan production and stomatal aperture assays as readouts of its bacterial signalling pathway. Null‐mutant complementation assays show that the photoactive Pr‐favoured Xcc BphP variants L193Q and L193N tend to negatively regulate xanthan production in vivo . In addition, our results indicate that strains expressing these variants also promote stomatal apertures in challenged plant epidermal peels, compared to wild‐type Xcc . The findings presented in this work provide new evidence on the Pr state of Xcc BphP as a negative regulator of the virulence‐associated mechanisms by light in Xcc . Abstract : The bacteriophytochrome photoreceptor Xcc BphP is involved in the light‐mediated virulence responses from the plant pathogen Xanthomonas campestris . Here, variants with single amino acid changes within its GAF domain favouring their Pr states were solved by X‐ray crystallography. Additionally, null‐mutant complementation assays showing that Pr‐favoured Xcc BphP variants negatively regulate xanthan production and promote stomatal apertures revealed that the alteration of the Xcc BphP photocycle impacts the signalling pathway in vivo .